CORONA VIRUS DISEASE (COVID-19): EPIDEMIOLOGICAL SPREAD OF THE PANDEMIC IN INDIA - AGGARWAL, KHUSHBOO; UPADHYE, VIJAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The corona viruses are a group of viruses that infect various mammals and have now proved to be pleomorphic. The CoVID-19 is the new corona virus that has proved to be hazardous to mankind and spreading among people as the clock ticks. It causes various flu-like symptoms many of which may prove to be fatal to anyone with a weak immune system and the elderly aged people. Originating from the Wuhan province of China, the disease spread to various parts of the world causing a ‘pandemic’. It has claimed the lives of many humans worldwide. It has also reached India now causing our government to impose rules to curb its spread by implementing Section 144 in the Indian Penal Code and Curfews and providing relief to the needy. The main aim of this review article to study and highlight the impact of global pandemic COVID-19 in India, Its widespread across various states of India and Impact on Indian Ecosystem, Business sector, Health Management, Social, cultural and behavioral aspects. It has hampered and almost shut down all India in the “Lock Down Stage” with only accessibility of citizens to purchase daily food items and medicinal requirements. Prevention is always better than Cure and only preventive measures, precautionary measures, Social distancing and maintain cleanliness and hygiene can only be the final solution to tackle a major global scourge.